Big data analytics in the context of internet of things and the emergence of real-time systems: a systematic literature review1. (2018) - Saheb, Tahereh
This paper is a systematic review of the papers on the field of IoT big data analytics (IoT BDA) with a concentration on real-time feature of the IoT systems. This paper shows that IoT BDA have challenged the relational databases in various forms, such as in terms of their flexibility, anomaly detection, real-time response, next-generation of hardware-software installment, and interoperability of multitude systems. This paper also explores the new feature of IoT BDA, challenges of security, privacy and interoperability within an IoT BDA systems, IoT BDA platforms, new and advanced analytical methods, and new system architectures and frameworks that are designed and developed by the papers. This paper also explores two main application of a mobile sensor and app in an IoT BDA system. This paper triggers broader discussion regarding future research agenda in the field of real time analysis of IoT big data both in practice and in theory.